Žižek, Slavoj. (2003). El sublime objeto de la ideología. Buenos Aires: Siglo XXI Editores. ISBN 978-1105-37-1 Número de páginas: 304. - Arias Sanabria, Carlos Arturo; Pontificia Universidad Javeriana (2015)
null